2012
DOI: 10.1099/vir.0.041509-0
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species infection of pigs with a novel rabbit, but not rat, strain of hepatitis E virus isolated in the United States

Abstract: Hepatitis E virus (HEV) is an important human pathogen. In addition to humans, HEV has also been identified in pig, chicken, mongoose, deer, rat, rabbit and fish. There are four recognized and two putative genotypes of mammalian HEV. Genotypes 1 and 2 are restricted to humans, while genotypes 3 and 4 are zoonotic. The recently identified rabbit HEV is a distant member of genotype 3. Here, we first expressed and purified the recombinant capsid protein of rabbit HEV and showed that the capsid protein of rabbit H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 50 publications
1
101
1
1
Order By: Relevance
“…Conversely, rabbit HEV strains can infect pigs and macaques (213,214), and they can replicate in two human cancer cell lines (96), suggesting the ability to adapt to other mammalian hosts. A study in China found no evidence of natural crossspecies infection with rabbit HEV (93).…”
Section: Scope and Duration Of Protective Immunity To Hev Following Imentioning
confidence: 99%
“…Conversely, rabbit HEV strains can infect pigs and macaques (213,214), and they can replicate in two human cancer cell lines (96), suggesting the ability to adapt to other mammalian hosts. A study in China found no evidence of natural crossspecies infection with rabbit HEV (93).…”
Section: Scope and Duration Of Protective Immunity To Hev Following Imentioning
confidence: 99%
“…Phylogenetic analysis of HEV isolated from humans and a variety of animal species proposed a revision of the taxonomy of the Hepeviridae (table 1) [10,11,12,13,14,15,16,17,18,19,20,21]. Two recent publications suggested classifying the molecularly characterised HEV in different taxonomic genera [14,15].…”
Section: Current Knowledge About the Pathogenmentioning
confidence: 99%
“…Whether rbHEV can be grouped as a separate genotype remains to be determined. Transmission experiments showed that some pigs infected with rbHEV-3 developed viraemia and shed virus with faeces [19]. However, epidemiologic studies showed that no transmission of rbHEV to pigs took place under natural conditions [88].…”
Section: Current Knowledge About the Pathogenmentioning
confidence: 99%
“…Genotypes 1 and 2 are restricted to humans, while genotypes 3 and 4 are zoonotic. The recently identified rabbit HEV is a distant member of genotype 3 and can infect pigs (Meng, 2011;Cossaboom et al, 2012). Rabbit HEVs with considerable genetic diversity are prevalent (15 % seroprevalence) in farmed rabbits in China (Geng et al, 2011).…”
Section: Epidemiological Linkmentioning
confidence: 99%